2020
DOI: 10.1021/acs.jafc.9b08309
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern, Gut Microbiota, and Alzheimer’s Disease

Abstract: Alzheimer's disease is the most common neurodegenerative disease. Until now, there has been no specific medicine that can cure Alzheimer's disease or effectively reverse the disease process. A good dietary pattern is an efficient way to prevent or delay the progression of the disease. Evidence suggests that diet may affect β-amyloid production and tau processing or may regulate inflammation, metabolism, and oxidative stress associated with Alzheimer's disease, which can be exerted by gut microbiota. The gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 102 publications
0
57
0
1
Order By: Relevance
“…Moreover, healthy dietary patterns can be beneficial for cognitive health and can show neuroprotective properties. The Mediterranean diet is deemed beneficial for AD patients as it is rich in many components such as legumes, fruits, vegetables, cereals, polyphenols, non-digestible carbohydrates, and unsaturated fatty acids [107]. Polyphenols (PPs) are naturally occurring bioactive compounds and the most abundant forms of antioxidants in the human diet [63].…”
Section: Diet and Food Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, healthy dietary patterns can be beneficial for cognitive health and can show neuroprotective properties. The Mediterranean diet is deemed beneficial for AD patients as it is rich in many components such as legumes, fruits, vegetables, cereals, polyphenols, non-digestible carbohydrates, and unsaturated fatty acids [107]. Polyphenols (PPs) are naturally occurring bioactive compounds and the most abundant forms of antioxidants in the human diet [63].…”
Section: Diet and Food Componentsmentioning
confidence: 99%
“…Prebiotics promote the growth of beneficial bacteria (including lactobacillus and bifidobacteria), and improve dysbiosis and the associated inflammatory conditions that may ameliorate cognitive impairment [111]. Conversely, the Western diet, consisting of saturated and high trans-fat, high sugar with fewer vegetables and fruits is considered a nutrient-imbalanced diet pattern [107]. This diet may cause metabolic syndromes and diseases and can increase the chances of AD development.…”
Section: Diet and Food Componentsmentioning
confidence: 99%
“…Aβ aggregation and memory impairment, as well as astrocyte activation, with a significant reduction in the expression levels of brain-derived neurotrophic factor (BDNF), while enhancing the expression of brain parenchymal cell apoptosis markers such as cytochrome C, Bax, caspase-9, and caspase-3 (Song et al, 2013;Calabrese et al, 2014;Badshah et al, 2016). Some microbiota had an anti-inflammatory activity identified on the basis of human clinical data, including F. prausnitzii (Sokol et al, 2008;Wang et al, 2014), E. rectale, B. longum (NK46), and B. fragilis (Lee et al, 2019;Markowiak-Kopeć andŚliżewska, 2020;Sun et al, 2020d;Zhang M. et al, 2020). Lee et al found that B. longum (NK46) was orally administered to 5 × FAD mice and induced anti-inflammatory effects (decrease in LPS levels, NF-κB activation, and TNF-α expression), changes in the intestinal microbiota composition of the recipients (increase in Bacteroides abundance and reduction in abundance of Firmicutes and Proteobacteria phyla), and suppression of Aβ accumulation in the hippocampus (Lee et al, 2019).…”
Section: Lps-induced Neuroinflammation Has Been Shown To Inducementioning
confidence: 99%
“…Accumulation of Aβ fibrils is thought to be an initiating factor in AD and necessary for the formation of tau aggregates (Goedert, 2018). Normal tau is essential for neuron extension configuration, cell polarization, and axonal transport, while hyperphosphorylation of tau leads to instability of the cytoskeleton, collapse of microtubules, synaptic failure, impairment of communication, and neuronal death (Zhang M. et al, 2020). Recently, the link between Aβ and tau in AD has been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, healthy dietary patterns show neuroprotective properties and can be beneficial to host cognitive health. On this regard, the Mediterranean diet is rich in many components considered helpful for AD subjects, among them vegetables, legumes, fruits, cereals and a high intake of unsaturated fatty acids and polyphenols [145]. In addition, oral bacteriotherapy has been recently identified as an accepted practice for the prevention and treatment of gastrointestinal infections [146] and inflammatory conditions [147,148].…”
Section: Novel Therapeutic Strategies: Dietbased Approaches and Faecal Transplantationmentioning
confidence: 99%